Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes. (June 2023) - Li, Jing; Tan, Yu-Fen; Zhou, Si-Qian; Liu, Shao; Wang, Wen-Xuan; Jiang, Yue-Ping; Long, Hong-Ping; Liu, Ji-Kai
Abstract: Three undescribed methylsuccinic acid derivatives, xylaril acids A–C, and two undescribed enoic acid derivatives, xylaril acids D–E, were isolated from the fungus Xylaria longipes . The structures of the undescribed compounds were deduced by spectroscopic means, including HRESIMS and 1D/2D NMR spectroscopy, as well as ECD calculations. The absolute configuration of xylaril acids A was further determined by single-crystal X-ray diffraction experiments. All the isolated compounds displayed neuroprotective activities against oxygen-glucose deprivation/reperfusion injury in PC12 cells by enhancing cell viability and inhibiting cell apoptosis. Graphical abstract: Five undescribed methylsuccinic acid and enoic acid derivatives with neuroprotective activities were isolated from the fungus Xylaria longipes . Image 1 Highlights: Five undescribed methylsuccinic and enoic acids were isolated from X. longipes. The structures were assigned by spectroscopic, XRD and computational methods. Four compounds exhibited neuroprotective effects.